Health access to immigrants: identifying gaps for social protection in health - Cabieses, Baltica; Oyarte, Marcela (Revista de Saúde Pública, 2020)
OBJECTIVE: To compare the access to and effective use of health services available among international migrants and Chileans. METHODS: Secondary analysis of the National Socioeconomic Characterization Survey (CASEN – Caracterización Socioeconómica Nacional), version 2017. Indicators of access to the health system (having health insurance) and effective use of health services (perceived need, appointment or coverage, barriers and need satisfaction) were described in immigrants and local population, self-reported. Gaps by immigrant status were estimated using logistic regressions, with complex samples. RESULTS: Immigrants were 7.5 times more likely to have no health insurance than local residents. Immigrants presented less perceived need than local residents, together with a greater lack of appointments (OR: 1.7 95%CI: 1.2–2.5), coverage (OR: 2.7 95%CI: 2.0–3.7) and unsatisfied need. The difference between immigrants and locals was not statistically significant in barriers to health care access (α = 0.005). CONCLUSIONS: Disadvantages persist regarding the access to and use of health services by immigrants as opposed to Chileans compared with information from previous years. It is necessary to reduce the gaps between immigrants and people born in Chile, especially in terms of health system access. This is the first barrier to effective use of services. The generation of concrete strategies and health policies that consider an approach of social participation of the immigrant community is suggested to bring the health system closer to this population.